Konsep Nuzulul Qur’an dan Asbābun Nuzūl: Implikasinya terhadap Metode Tafsir Ayat-Ayat Al-Qur’an - Anshory, Muhammad Isa; Khamdani, Agus Walid; Hidayah, Nur (Lembaga Yasin AlSys, 2025)
This article is motivated by the importance of understanding the historical and situational context in interpreting the Qur’an, particularly through the study of the foundational concepts of Nuzulul Qur'an and Asbābun Nuzūl. The primary aim of this study is to analyze the implications of understanding these two concepts for the methods of interpreting Qur’anic verses, both in classical and contemporary exegesis traditions. The study employs a qualitative analytical approach through a literature review of Islamic scholarly works related to the central theme. The findings indicate that Asbābun Nuzūl plays a significant role in clarifying the meaning of verses, preventing misinterpretation, and bridging the divine message with modern social realities. The integration of textual (linguistic) and contextual (revelatory circumstances) analysis has proven to enrich the exegetical methodology, making it more responsive to contemporary challenges. The study concludes by emphasizing the urgency of contextual approaches in the development of Qur’anic interpretation, ensuring that the values of revelation remain relevant and applicable to the lives of present-day Muslim communities.